Wrightia tinctoria (Indrajav)-Apocynaceae: Overview (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Wrightia tinctoria is a perennial ornamental woody plant; belong to Apocynaceae family available throughout India. Various parts of this plant like stem bark, leaves, flowers and seed have been known to possess medicinal properties like anti-inflammatory, antiviral, antibacterial, wound healing, anticancer, antiulcer etc. The present paper is an attempt to provide a detailed botanical description, classification, phytochemical and pharmacological study of the plant.